Biophysical and molecular interactions of enantiomeric piperonal-derived trans β-aryl-δ-iodo-γ-lactones with cancer cell membranes, protein and DNA: Implications for anticancer activity - Włoch, Aleksandra; Sengupta, Priti; Szulc, Natalia; Kral, Teresa; Pawlak, Aleksandra; Henklewska, Marta; Pruchnik, Hanna; Sykora, Jan; Hof, Martin; Gładkowski, Witold (International journal of biological macromolecules, 2025)
Developing novel anticancer agents requires understanding their interactions with biological systems at both the cellular and molecular levels. Enantiomeric lactones have demonstrated notable cytotoxic activities against various cancer cell lines. Building on this foundation, we investigated enantiomeric piperonal-derived trans-β-aryl-δ-iodo-γ-lactones ((-)-(4S,5R,6S) and (+)-(4R,5S,6R)), focusing on their impact on cancer cells membrane (Jurkat and GL-1), model membranes, and biomacromolecules such as human serum albumin (HSA) and DNA. Also, the cytotoxicity toward red blood cells and the antitumor activity of the compounds were evaluated against a set of canine lymphoma and/or leukemia cell lines. Membrane interaction studies revealed that both enantiomers interact with the hydrophobic core of lipid bilayers, enhancing lipid acyl chain packing, with the (-)-(4S,5R,6S) isomer showing a stronger impact on membrane fluidity. Comprehensive spectroscopic and theoretical studies revealed distinct stereochemical differences in binding affinities to HSA, where the (-)-(4S,5R,6S) isomer showed higher binding affinity and significant hydrophobic interactions. Detailed biological studies demonstrated that both enantiomers exhibit antiproliferative and proapoptotic activities, with the (-)-(4S,5R,6S) enantiomer showing higher activity. This study underscores the biological activity and interactions of enantiomeric iodolactones derived from piperonal with biomacromolecules, providing comprehensive insights into their biophysical behavior and potential anticancer properties.
Keywords: buněčná membrána; psi; Lactones; Lipid Bilayers; stereoizomerie; Enantiomeric iodolactones; Humans; Dogs; Jurkat buňky; HSA; Hydrophobic and Hydrophilic Interactions; Single-molecule fluorescence spectroscopy; Antineoplastic Agents; Jurkat Cells; lidský sérový albumin; lidé; zvířata; Stereoisomerism; DNA; lipidové dvojvrstvy; Serum Albumin, Human; nádorové buněčné linie; protinádorové látky; laktony; Animals; Cell Membrane; Cell Line, Tumor; cancer cell membrane; hydrofobní a hydrofilní interakce